2008
DOI: 10.1111/j.1524-4733.2007.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

An Asian Regional Analysis of Cost-Effectiveness of Early Irbesartan Treatment versus Conventional Antihypertensive, Late Amlodipine, and Late Irbesartan Treatments in Patients with Type 2 Diabetes, Hypertension, and Nephropathy

Abstract: Although the absolute results varied in different settings, reflecting differences in epidemiology, management, and costs, early irbesartan treatment was a cost-effective alternative in the Asian settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The majority of the studies based their efficacy data on two clinical trials, ie, IDNT and IRMA-2. All studies were modeling ones, using a Markov model, with the majority being cost-effectiveness analyses8694 or cost-consequence analyses,9599 while one was a cost utility analysis 100. Studies were done either from a third party payer perspective or from a health care payer perspective.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies based their efficacy data on two clinical trials, ie, IDNT and IRMA-2. All studies were modeling ones, using a Markov model, with the majority being cost-effectiveness analyses8694 or cost-consequence analyses,9599 while one was a cost utility analysis 100. Studies were done either from a third party payer perspective or from a health care payer perspective.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Life expectancy for irbesartan was 8.58 life years in a 25-year time horizon versus 8.13 life years with amlodipine 88,91,9496. Five studies comparing early versus late irbesartan treatment showed that early irbesartan is more effective than late irbesartan 86,87,92,98,100. Life years gained with irbesartan were 12.17 versus 11.27 with late irbesartan treatment.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Fourteen evaluations for losartan [32,39-47] were based on The Reduction of Endpoints in Non-insulin Dependent Diabetes Mellitus with the Angiotensin II Antagonist Losartan (RENAAL) trial [62]. Eighteen evaluations of irbesartan [48-60] used data from the Irbesartan in Diabetic Nephropathy Trial (IDNT) [68] to assess the cost-effectiveness for patients with type 2 diabetes and overt nephropathy before 2004. Later the Irbesartan in Reduction of Microalbuminuria-2 (IRMA-2) [69] trial was added into the model to expand the progress of diabetic renal development from nephropathy back to the onset of MiA.…”
Section: Resultsmentioning
confidence: 99%
“…These five studies were based on the IDNT trial and a Markov model with five stages (from ‘overt nephropathy’ via ‘double of serum creatinine’ , ‘ESRD + dialysis’ and ‘ESRD + transplant’ to ‘death’) was developed to evaluate life expectancy and lifetime cost. In particular, Palmer et al combined the IRMA-2 trial with the IDNT trial and applied a seven-stage Markov model, extrapolating the Markov model with a previous MiA state [48,49,51-60]. ‘Early irbesartan’ (standard antihypertensive therapy plus irbesartan at the onset of MiA) was then compared with conventional therapy and ‘late irbesartan’ or ‘late amlodipine’ (standard antihypertensive therapy plus administration of irbesartan/amlodipine once the patients reach the advanced diabetic nephropathy stage).…”
Section: Resultsmentioning
confidence: 99%
“…China-specific ESRD treatment modalities (haemodialysis, peritoneal dialysis, or renal transplant) and survival were also incorporated. 42,43 Mortality associated with hypoglycaemia was not captured in the analyses.…”
Section: Modelmentioning
confidence: 99%